Upaya Meningkatkan Kedisiplinan dalam Pembelajaran melalui Teknik Behavioral Contract pada Siswa SMK Negeri 2 Lamongan - Mar'ah Fatinah; Nadhirotul Laily (PT. Penerbit Tiga Mutiara, 2024)
This research discusses efforts to increase discipline in learning through behavioral contract techniques in students at SMK Negeri 2 Lamongan. This research aims to teach directly the Behavior Contract technique, increase the learning effectiveness of students at SMK Negeri 2 Lamongan, and address the low learning effectiveness of students at SMK Negeri 2 Lamongan. This type of research is quantitative research. The problem in this research is that in implementing learning, students often choose lessons they only like and don't want to go to class and often hang out in the canteen. This causes a lack of application of scientific disciplines in learning for students. Researchers also use a behavioral approach because this approach assumes that all behavior, both adaptive and maladaptive, can be learned. This approach can be carried out in depth with groups of students who have a habit of being undisciplined in learning. Researchers conducted interviews and distributed questionnaires to students with the results of the level of learning discipline before receiving the intervention and after receiving intervention through the behavior contract technique, which was different, the result of which was that the learning discipline of students at SMK N 2 Lamongan class XI before being given the behavior contract technique was in the low category, after being given it. intervention through the behavior contract technique resulted in an increase in categories starting from the very low category to the low and high categories which experienced a significant increase. The results of this research were obtained from the results of the Wilcoxon Signed test, obtained a Z value of -1.342 and an asymp value of sig. (2-tailed) 0.180 is smaller than the alpha level of 5% (0.05), so the conclusion is that there is a difference in the learning discipline of students at SMK N 2 Lamongan class XI before and after being given the behavior contract intervention.